SPONTANEOUS TRIPLET PREGNANCY DURING MULTIDRUG THERAPY TREATMENT FOR LEPROSY – A CASE REPORT (Journal of Pharmaceutical Negative Results, 2023)
Leprosy is a chronic disease affecting mainly skin, mucous membranes, and peripheral nerves due to Mycobacterium leprae and can be exacerbated during pregnancy. Spontaneous triplet pregnancies are rare; however, these multiple pregnancies are associated with increased risk of maternal and neonatal morbidity and therefore should be prevented. Both leprosy and multiple gestation independently are risk factors for prematurity and low birth weight. This article describes a patient who had both these high-risk factors in her pregnancy undesirably due to spontaneous conception with Triamniotic-Trichorionic triplets while undergoing leprosy treatment with multidrug therapy (MDT) consisting of dapsone, rifampicin and clofazimine.